Dichotomy of the human T cell response to leishmania antigens. II. Absent or Th2-like response to gp63 and Th1-like response to lipophosphoglycan-associated protein in cells from cured visceral leishmaniasis patients - Kurtzhals, J. A. L. (1994)
The T cell response to different Leishmania donovani antigens was investigated using peripheral blood mononuclear cells (PBMC) from Kenyans cured of visceral leishmaniasis and non-exposed Danes. Crude promastigote and amastigote antigens both induced proliferation and interferon-gamma (IFN-γ) production in PBMC from cured patients, while cells from non-exposed donors gave weak responses. A similar pattern was induced by lipophosphoglycan-associated protein (LPGAP). By contrast, the major surface protease of Leishmania, gp63, induced only a weak proliferative response without IFN-γ production in five of 17 samples from cured patients. Four of the five responding cultures produced IL-4, i.e. the response to this antigen was of the Th2 type. Furthermore, sera from acutely ill visceral leishmaniasis patients contained high levels of IgG antibodies to gp63. The Th2-like response to gp63 in patients cured of visceral leishmaniasis differs from the Th1-like response to the same antigen observed in patients cured of cutaneous leishmaniasis.